2017
DOI: 10.17338/trainology.6.1_31
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the submaximal version of the Yo-Yo intermittent recovery test in elite youth soccer

Abstract: Objectives:To determine the test-retest reliability of the submaximal version of the Yo-Yo Intermittent Recovery Test -Level 1 (Yo-Yo IR1-sub), which is a valid aerobic assessment.Design: Test-re-test. Methods: Elite youth soccer players (n = 10, age: 18.8 ± 0.5 years, height: 181.1 ± 4.9 cm, body mass: 74.2 ± 7.6 Kg) completed the Yo-Yo IR1-sub on two consecutive weeks to determine the reliability of a non-exhaustive alternative to maximal aerobic testing. Relative and absolute reliability of the Yo-Yo IR1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
5
16
0
Order By: Relevance
“…We observed similar reliability for HRpost1 in the present study compared to the work of Lambert et al (25) but better than that of Owen et al (31). Differences in the running speeds used and how HRR was calculated is probably an explanation for the variation from pervious work.…”
Section: Reliability Of Selected Hr Measures In Swtsupporting
confidence: 80%
See 2 more Smart Citations
“…We observed similar reliability for HRpost1 in the present study compared to the work of Lambert et al (25) but better than that of Owen et al (31). Differences in the running speeds used and how HRR was calculated is probably an explanation for the variation from pervious work.…”
Section: Reliability Of Selected Hr Measures In Swtsupporting
confidence: 80%
“…In conclusion, the present study showed that selected HR measures derived from a simple continuous and submaximal test with a short duration (≤ 5min) has acceptable reliability that is agreeable with faster submaximal tests that have been previously proposed for soccer players (3,20,30). Discrepancies between the results of previous studies when evaluating the reliability and validity of HRex collected at different time points (i.e., 2, 3, 4, 6 and 9 min) (4,20,21,23,31,37) may also be related to the submaximal test protocol including its continuous or intermittent nature and the final speed reached as important determinant factors. The results of present study also suggest implementing a continuous protocol with a slower speed may reduce the number of habituation sessions and the feasibility of using of submaximal tests as part of the player monitoring process.…”
Section: *** Figure 3 Near Here ***mentioning
confidence: 43%
See 1 more Smart Citation
“…This is particularly evident for the HR measures obtained during the passive recovery period, which is a potentially novel aspect of the test for some players. In this respect, work by Owen et al (2017) only incorporated two trials and therefore, the inclusion of an additional trial may result in lower levels of variability for each of the HR measures obtained during the 6 min Yo-Yo IR1 with a passive recovery period. This in turn will have an impact upon the sensitivity of the test, as superior levels of reproducibility will increase the possibility of detecting a 'real change'.…”
Section: Resultsmentioning
confidence: 99%
“…Deprez et al (2014) reported little variance (CV's between 1.1 and 4.1%) when assessing the test-retest reliability of HR measures (%HRmax) in a cohort of non-elite youth soccer players, at different levels during the Yo-Yo IR1 and at 1 and 2 min post-test. Moreover, recent research by Owen, Jones and Comfort (2017), reported that HR measures obtained at the end of a 6 min Yo-Yo IR1 and at 30, 60, 90 and 120 sec during a 2 min passive recovery, were determined to be reliable in elite youth soccer players aged 18.8 ± 0.5 years. Nevertheless, it is necessary to gain population specific (i.e.…”
Section: Introductionmentioning
confidence: 98%